Kinetics on the Oxidation of Aminoiminomethanesulfonic Acid by Hypochlorous Acid: A Novel Product in the Chlorination of Aminoiminomethanesulfonic Acid. Issue 31 (30th July 2021) - Hu, Ying; Li, Wei; Wang, Guichang; Pan, Changwei; Ji, Chen; Gao, Qingyu
Abstract: The oxidation of aminoiminomethanesulfonic acid (AIMSOA) by HOCl is too fast to be traced in both acidic and neutral solutions, while extreme alkalinity will hasten the decomposition of AIMSOA. Nonetheless, in weakly alkaline solutions the oxidation kinetics were monitored successfully by stopped flow at 25 °C. The results show that the rate law is first order with respect to both [HOCl]tot and [AIMSOA] but shows an inverse dependence on [OH − ]. The calculated k HOCl values of (9.2±0.2)×10 6  M −1  s −1 and a statistically insignificant k OCl ‐ value indicate that the conjugate acid HOCl is regarded as the primary oxidant. The reaction is supposed to be a Cl + transfer mechanism followed by the formation of a novel unreported oxidation product, AIMSOA‐chloramine. Various technologies were employed to investigate the structure and decomposition of AIMSOA‐chloramine. The above evidence showed that the product, a kind of chloramine rather than sulfate, was characterized by a distinct structure consisting of N−Cl bond. The chloramine could also slowly decompose to sulfate and chloride due to the cleavage of both C−S and N−Cl bonds. Based on the results, the mechanism involving the production of chloride and sulfate from the oxidation of AIMSOA in Cl‐containing oxides ‐ thiourea system should be excluded. In addition, the results also provide additional insights into the bromination for the HOBr‐AIMSOA reaction, in which priority may be given to the formation of bromamine. Abstract : In this work we study the kinetics and mechanism of hypochlorous acid‐aminoiminomethanesulfonic acid (AIMSOA) system for the first time, and find the formation of a novel unreported oxidation product, AIMSOA‐chloramine. Based on the decomposition kinetics, the high stability of chlorination product in aqueous solution indicates reaction between hypochlorous acid and aminoiminomethanesulfonic acid is excluded for producing sulfate in chlorite(chlorine dioxide)‐thiourea nonlinear reaction system. The results provide additional insights into the bromination for the HOBr‐AIMSOA reaction, in which priority may be given to the formation of bromamine.